Long-term outcome of left atrial appendage occlusion with multiple devices. (1st December 2021) - Radinovic, Andrea; Falasconi, Giulio; Marzi, Alessandra; D'Angelo, Giuseppe; Limite, Luca; Paglino, Gabriele; Peretto, Giovanni; Frontera, Antonio; Fierro, Nicolai; Sala, Simone; Della Bella, Paolo; Mazzone, Patrizio
Abstract: Background: To evaluate long-term efficacy of left atrial appendage occlusion with multiple devices. Methods: All consecutive patients who underwent left atrial appendage occlusion (LAAO) with a follow-up of at least 4 years, were included in this single center, retrospective registry. No specific exclusion criteria were applied. LAA occlusion was performed with the Watchman, Watchman FLX, Amplatzer Cardiac plug or Amplatzer Amulet occluder devices. Results: A total of 224 consecutive patients underwent LAAO occlusion. Mean age was 72.5 ± 9.0 years. A history of stroke was present in 29%, TIA in 8.5% and a previous episode of bleeding in 64.7% of patients. In 63% there was a contraindication to oral anticoagulants. The average CHADS-VASc was 4.0 ± 1.6 and the average HAS-BLED was 3.4 ± 1.3. There was a reduction of strokes of 72.9%, thromboembolic events of 59.7% and major bleeding events of 70.9% compared to historic data. During follow-up, 48.3% of the ischemic and major bleeding events occurred within the first year. The annual mortality rate of 7.5 deaths/ 100 patients years. There were no significant differences in terms of outcome between the devices used and there were no late events associated with any device. The main antithrombotic regimen in the long term was with single antiplatelet therapy and the second one was no therapy. Conclusion: LAAO is a safe and effective procedure, that reduces ischemic and bleeding events in the long-term, regardless of the type of device used, in AF patients at high risk of ischemic stroke and major bleeding, without the need of anticoagulation. Highlights: This is the first spontaneous real-world registry to report long-term outcomes of LAAO with multiple devices in AF patients. LAAO is a safe and effective alternative to oral anticoagulation at a 4-year follow-up regardless of the type of device used.